Ensino de gramática como habilidade : efeitos perceptíveis na acuidade da produção linguística de jovens aprendizes de língua inglesa - Terenzi, Daniela (2009)
This dissertation presents the results of an investigation that aimed at verifying the effects of teaching-learning grammar as skill on accuracy of young learners attending a course based on four different themes. Besides being thematic, the course design followed the grammar as skill approach and theory to guide the activities and the development of the classes. Based on qualitative data analysis, we present the results of our study, which reveal students involvement and accuracy progress when exposed to meaning-focused formal language studies. Students proved able to notice language aspects, structure and use them in verisimilar contexts, specially concerning grammatical and linguistic aspects that had been focused in classes. We have based our discussion and pedagogical activity design mainly on Batstone (1994) and Larsen-Freeman (2004). The activities proposed in the course that has served as the context for data collection are available at the appendix section of this dissertation. Our research is likely to contribute with the discussion considering the role of grammar teaching in classrooms as well as to provide professionals in the area with a better comprehension of this contemporary approach, which has not been widely investigated yet.